Analisis SWOT Produk Pembiayaan Di Bank Muamalat Pada Masa Pandemi - Muhamad Fauzin Nur; Lilik Rahmawati (Jurnal Perbankan Syariah)
Financing is a banking product that is needed by society. As part of the business run by Bank Muamalat, financing during the pandemic is interesting to study, considering that the pandemic has had an impact on Islamic banking. This study aims to determine the performance and identification of internal and external conditions of financing at the Bank Muamalat Surabaya Darmo branch office using SWOT analysis. The study used a qualitative descriptive approach with SWOT as an analytical tool. Consists of two types of data, those are primary and secondary data obtained using interviews, observation, questionnaires, and documentation techniques. Data triangulation was done by interview method. The study results show that the financing performance at Bank Muamalat Surabaya Darmo branch office during the pandemic continued to run by focusing on the Islamic segment for the productive financing and consumptive financing channelled to Talang haji funds, multipurpose funds, and mortgages. The current financing position is in the first quadrant which supports the implementation of an aggressive strategy.